The Relationship of Independent Learning and Time Management with Academic Achievement of 2013 Stambuk Students Study Program in Economics Education Department, State University of Medan - Nurhasanah (Outline Publisher, 2022)
This study aims to determine the relationship between learning independence and time management with academic achievement of students in the 2013 Stambuk Education Study Program, State University of Medan. The population in this study were students of the 2013 Commerce Administration Study Program, Faculty of Economics, State University of Medan, amounting to 109 people. The sample used in this study was 54 people using the random sampling technique, sampling refers to Arikunto's opinion. Data collection techniques used in this study were observation, documentation and questionnaires. The results state that there is a positive and partially significant relationship with student academic achievement with sig < i.e. 0.000 <0.05 and with tcount > ttable (4.583>1.67). Simultaneously, the variables of learning independence (X1) and time management (X2) were positively and significantly related to the variable of student academic achievement (Y) with a value of sig < , namely 0.000 <0.05.